Crystallization kinetics of high‐density and low‐density polyethylene on carbon nanotubes. Issue 4 (20th February 2019) - Depan, Dilip; Khattab, Ahmed; Simoneaux, Austin; Chirdon, William
Abstract: This study presents a comparative analysis of the crystallization behavior of low‐density polyethylene (LDPE) and high‐density polyethylene (HDPE) nanocomposites. Carbon nanotubes (CNTs) were used as a nucleating agent to generate a nanohybrid shish‐kebab architecture. Materials characterizations were performed to evaluate the crystal morphology and crystallization kinetics using scanning electron microscopy (SEM) and differential scanning calorimetry (DSC), respectively. The lamellae of polyethylene were always found to grow laterally on the tube axis of CNTs. The parameters of the Avrami model for primary crystallization were determined. SEM indicated the crystal morphology changed from spherulitic to disk‐shaped with the addition of CNTs, while DSC‐based thermal examination indicated that the CNTs can provide nucleation sites to polyethylene to accelerate the crystal growth rate. HDPE was found to crystallize faster than LDPE on CNTs. The highly branched nature of LDPE's macromolecular chains are known to cause reduced chain mobility, which resulted in lower crystallinity values with smaller crystallite sizes for LDPE in this study. In comparison, the more linear HDPE chains have an increased polymer density and chain mobility, resulting in an improved nucleation ability of HDPE chain segments on CNTs. Abstract : This work presents a comparative analysis of high‐density polyethylene (HDPE) and low‐density polyethylene (LDPE) nanohybrid shish‐kebab formation on carbon nanotubes (CNTs). As HDPE is highly linear and has tightly packed polymer chains, it forms thicker crystals than LDPE. Highly branched LDPE requires more energy and time to crystallize on CNTs, resulting in more amorphous regions. A comparative analysis of crystallization kinetics offers new insight into the origin of the nucleating effects and quantitatively determines their impact on crystallization.